Mild donor-π-mild acceptor (mD-π-mA) benzimidazole-based deep blue fluorophores with hybridized local and charge transfer (HLCT) excited states for OLEDs. Issue 3 (3rd July 2022) - Devesing Girase, Jaipal; Mukherjee, Susmita; Chakrabarti, Tanwistha; Patel, Sabita; Perumal, Ajay; Vaidyanathan, Sivakumar
Abstract : The design of an efficient pure blue emitter to achieve stable, long operating organic light-emitting diode (OLED) devices still poses a significant challenge. Although through phosphorescence and thermally activated delayed fluorescence concepts, efficient and stable monochrome green and red OLEDs can be realized, the design of stable and efficient blue emitter has been a significant challenge. All efforts so far have resulted in severe efficiency roll-off and limited device lifetime. Therefore, developing efficient blue-emitting fluorescence materials with little or no efficiency roll-off is of great importance for commercial display OLEDs. In this context, we have designed and synthesized two pure blue fluorescence light-emitting materials that are thermally stable and have improved photophysical properties: 2-(4 ″ -(1-(4-(tert-butyl)phenyl)-4, 5-diphenyl-1 H -imidazol-2-yl)-[1, 1′:4′, 1 ′′ -terphenyl]-4-yl)-1-phenyl-1 H -benzo[ d ]imidazole (PTBIBI) and 2-(4 ′′ -(4, 5-diphenyl-1-(3-(trifluoromethyl)phenyl)-1 H -imidazol-2-yl)-[1, 1′:4′, 1 ′′ -terphenyl]-4-yl)-1-phenyl-1 H -benzo[ d ]imidazole (MCFBIBI) . These emitters possess a hybrid local and charge-transfer (HLCT) state and have high photoluminescence quantum yields (>90%). The doped devices based on PTBIBI display a reasonably good device performance with the Commission International de l'Eclairage (CIE) coordinates of (0.15, 0.06) in the deep blue region and g maximum luminance of 6559 cd m −2 at a very low turn-on voltage (3.2 V) corresponding to the bandgap value of the blue emitter.